Representasi Kepemimpinan Presiden Joko Widodo Pada Berita Korupsi di Media Indonesia (President Joko Widodo's Leadership Representation on Corruption News in Indonesian Media) - Saiyidinal Firdaus (Indonesian Language Education and Literature, 2022)
Indonesia ranks 89th out of 180 countries and is still a corrupt country. As the leader of the country, the president is expected to make Indonesia no longer a corrupt country. This study seeks to analyze corruption news in the March 31, 2019 edition of Media Indonesia in order to raise views on Joko Widodo as a social actor. This can be known through the analysis of language structure, cognitive processes, and the meaning of discourse based on the context of the "2019 Presidential Election". This study applies a qualitative approach with van Dijk's critical discourse analysis (AWK) approach. The results show that the text of corruption news in the March 31, 2019 edition of Media Indonesia aims to raise Jokowi's image ahead of the 2019 Presidential Election. The context of the "2019 Presidential Election" shows a tremendous influence for the Media Indonesia editorial team to produce corrupt news texts associated with Jokowi, as well as his candidacy, himself as a presidential candidate in the 2019 presidential election.Indonesia menempati posisi ke-89 dari 180 negara dan masih menjadi negara korup. Sebagai pemimpin negara, presiden diharapkan menjadikan Indonesia tidak lagi menjadi negara yang korup. Penelitian ini berupaya untuk menganalisisÂ berita korupsi di Media Indonesia edisi 31 Maret 2019Â dalamÂ memunculkan pandangan kepada Joko Widodo sebagai aktor sosial.Â Hal ini dapat diketahui melalui analisis struktur bahasa, proses kognitif, dan makna wacana berdasarkan konteks â€œPilpres 2019â€. Penelitian ini menerapkan ancangan kualitatif dengan pendekatan analisis wacana kritis (AWK) van Dijk. Hasil penelitian menunjukkan bahwa teks berita korupsiÂ diÂ Media Indonesia edisi 31 Maret 2019 bertujuan untuk mengangkat citra Jokowi menjelang Pilpres 2019. Konteks â€œPilpres 2019â€ menunjukkan pengaruh yang luar biasa bagi tim redaksi Media Indonesia untuk memproduksi teks berita korupsi yang dikaitkan dengan Jokowi, serta pencalonan kembali dirinya sebagai calon presiden pada Pilpres 2019.